LES COMPOSITES A BASE DE POLYSTYRENE /FARINE DE GRIGNON D’OLIVE: EFFET DU TAUX DE CHARGE SUR LES PROPRIETES MORPHOLOGIQUES, THERMIQUES ET D'ABSORPTION D'EAU - BOUSSEHEL, H.; MEGHEZZI, A.; NEBBACHE, N. (Courrier du Savoir; Vol. 23 (2017): COURRIER DU SAVOIR (JUIN), 2017)
In this study, the influence of the filler content of olive stone flour (OSF) reinforced polystyrene composites (PS) on the morphological, thermal and water absorption properties were investigated. The composite was prepared by melt-mixing method, followed by compression molding process. Different filler loadings were prepared; namely, 0%, 10%, and 30% weight percent. It found that the incorporation of olive stone flour with polystyrene matrix result a poor interfacial adhesion between them. In other hand the increasing of the OSF content decreased clearly the degradation temperature of these composites. However, the water absorption in these species increased with the addition of OSF.